2020
DOI: 10.1101/2020.03.24.006510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photoperiod-dependent developmental reprogramming of the transcriptional response to seawater entry in Atlantic salmon (Salmo salar)

Abstract: The developmental transition of juvenile salmon from a freshwater resident morph (parr) to a seawater (SW) migratory morph (smolt) requires a range of physiological adaptations, including the capacity to hypo-osmoregulate. This process, known as smolting, involves both photoperiod-dependent preparative changes before SW is encountered, and activational changes stimulated by exposure to SW. To explore the relationship between these two aspects we undertook experiments in which physiological and transcriptomic r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Heatmaps were made by first discarding genes that had normalized read counts <50 in all assayed tissues, before using J‐Express (v. 2012) (Dysvik & Jonassen, 2001) to generate heatmaps using high‐level mean and variance normalization, with complete linkage clustering and Euclidean distance measure. Gene expression in gills of salmon exposed to saltwater for 24 hr was examined using RNA‐Seq data obtained from Array Express (accession number E‐MTAB‐8276), described previously in Iversen et al (2020). Sequence reads were filtered using Cutadapt with parameters ‐q 20 ‐O 8 and ‐m 40 and mapped to the salmon gene models with Bowtie2 using default settings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heatmaps were made by first discarding genes that had normalized read counts <50 in all assayed tissues, before using J‐Express (v. 2012) (Dysvik & Jonassen, 2001) to generate heatmaps using high‐level mean and variance normalization, with complete linkage clustering and Euclidean distance measure. Gene expression in gills of salmon exposed to saltwater for 24 hr was examined using RNA‐Seq data obtained from Array Express (accession number E‐MTAB‐8276), described previously in Iversen et al (2020). Sequence reads were filtered using Cutadapt with parameters ‐q 20 ‐O 8 and ‐m 40 and mapped to the salmon gene models with Bowtie2 using default settings.…”
Section: Methodsmentioning
confidence: 99%
“…We also screened the sweeps for genes differentially expressed in juvenile fish exposed to saltwater by re-analysis of a recently published RNA-Seq dataset (Iversen et al, 2020) from salmon gills. This revealed that 14 of the genes in the sweeps were differentially expressed (p adj < .001) in at least one sampling point in fish challenged by saltwater for 24 hr at six sampling points over a 110-day period (File S3).…”
Section: Genes In Selective Sweeps Differentially Expressed In the Gi...mentioning
confidence: 99%